The British General Election of 1992 - Butler, D. author. aut Link
XI, 391 p.
Keywords: This volume is the 14th in a series of studies begun in 1945 which have chronicled every postwar election. The historical background, the party preparation and the events of the campaign are recorded, together with analyses of the polls, the press, broadcast coverage and the candidates.